A NEW GENUS AND SPECIES OF THE FAMILY TRACHYPACHIDAE (COLEOPTERAN, ADEPHAGA) FROM THE UPPER LADINIAN (MIDDLE TRIASSIC) OF MONTE SAN GIORGIO - LAURA STRADA; MATTEO MONTAGNA; ANDREA TINTORI (Rivista Italiana di Paleontologia e Stratigrafia, 2014)
A new genus and species of fossil Trachypachidae Praedodromeus sangiorgiensis gen. n sp. n. (Coleoptera, Trachypachidae, Eodromeinae), with well developed asymmetrical mandibles, shorter than the head, subrectangular pronotum and slender tibiae, longer than femora, is described from the Kalkschieferzone (uppermost member of the Meride Limestone) of the Swiss side of Monte San Giorgio. Trachypachidae are terrestrial Coleoptera well represented in the Mesozoic fossil record by the extinct family Eodromeinae. Up to now, more than 33 fossil species belonging to 13 genera of Eodromeinae have been described. The new species is part of a collection of fossil insects that includes members of at least six different orders. Based on the ecology of corresponding extant taxa, this insect assemblage provides new insights on the paleoenvironment of Monte San Giorgio area during the Late Ladinian. The assemblage includes terrestrial taxa that support the presence of emerged land and taxa with long-lasting aquatic larval stage (as Plecoptera and Ephemeroptera) that confirm the presence of stable fresh water basins.